Rancang Bangun Aplikasi Penilaian Kinerja Karyawan Menggunakan Metode Graphic Rating Scale Berbasis Web Pada PT Nipsea Paint and Chemicals Makassar - Sari, Dinda Anggraini Puspita; Nurcahyawati, Vivine; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PT Nipsea Paint and Chemicals Makassar (Nippon Paint Makassar) is one of Nippon Paint Gresik's corporate branches. The Nippon Paint Makassar is a company used for the storage of paint products that will be distributed to parts of Sulawesi such as South Sulawesi, West Sulawesi, and Central Sulawesi. Every year there are performance assessment process, when conducting assessment there are several problems among others the performance assessment report of previous period is missing, there is no weight in performance assessment on the every indicators used as a priorityÂ  for working to be met by employees on the company, performance assessments conducted using manual calculations with microsoft excel that are carried out repeatedly so as to cause the risk of calculation is not appropriate, Sometimes employee performance assessment reports have a delay set in the deadline. Based on the problems outlined, the solution required for Nippon Paint Makassar is an employee performance assessment application using the Graphic Rating Scale method. Results obtained from the performance assessment application that has been designed is this application can help the Head of Depo in performing the performance assessment process easily with accurate results.